Sociological and mathematics educational values: an intersection of need for effective mathematics instructional contents delivery - Liman, Mukhtar Alhaji; Salleh, Mohamad Johdi (Centre for Promoting Ideas, USA, 2013)
Sociological and mathematics educational values are two key components worthy of integration for effective mathematics instructional contents delivery in this era of globalized world. The paper examines values attached to these components and its applicability in an ongoing mathematics classroom. The study employs qualitative methodological technique with interviews as a source of data. 3-service mathematics teachers teaching mathematics in different senior secondary schools participated in the study. The findings reveal that mathematics teachers are aware and had minimum understanding of these components of values inculcation in their mathematics teaching and learning. Suggestions are offered on how to improve sociological and mathematics educational values for effective mathematics instruction.